PENGEMBANGAN MODEL SUPPLY CHAIN PISANG MAS DI JAWA TIMUR - Wilson Sanada; I Gede Agus Widyadana; Herry Christian Palit (Jurnal Titra, 2014)
Musa acuminata paradisiaca is one of banana varieties, has a high demand in East Java thus highly potential to be developed. The highest production sites are located at Malang and Lumajang. Unfortunately, this type of banana are perishable that limited the selling period. An alternative way to solve is via improving the supply chain management. In this research, we developed some supply chain models and evaluate there performance using simulation with Vensim software. We used sales profit, lost sales, oversupply and availability to measure performance of the models, supply chain management at Malang and Lumajang. The results show that supply chain at Lumajang performed better than Malang interms of sales profit, lost sales and availability.